2018
DOI: 10.1142/s2010194518600960
|View full text |Cite
|
Sign up to set email alerts
|

Different Ways to Estimate Graviton Mass

Abstract: An experimental detection of graviton is extremely hard problem, however, there are different ways to evaluate a graviton mass if it is non-vanishing. Theories of massive gravity or theories with non-vanishing graviton mass initially have a number of pathologies such as discontinuities, ghosts etc. In last years theorists found ways to overcome weaknesses of such theories meanwhile observational features are also discussed. In the first publication reporting about the discovery of gravitational waves from the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…Constraints on speed of gravitational waves have been found −3 × 10 −15 < (v g − c)/c < 7 × 10 −16 [68]. Graviton energy is E = hf , therefore, assuming a typical LIGO frequency range f ∈ (10, 100), from the dispersion relation one could obtain a graviton mass estimate m g < 3 × (10 −21 − 10 −20 ) eV which a slightly weaker estimate than previous ones obtained from binary black hole signals detected by the LIGO team [78].…”
Section: Observational Constraints On Graviton Mass From Observationsmentioning
confidence: 78%
“…Constraints on speed of gravitational waves have been found −3 × 10 −15 < (v g − c)/c < 7 × 10 −16 [68]. Graviton energy is E = hf , therefore, assuming a typical LIGO frequency range f ∈ (10, 100), from the dispersion relation one could obtain a graviton mass estimate m g < 3 × (10 −21 − 10 −20 ) eV which a slightly weaker estimate than previous ones obtained from binary black hole signals detected by the LIGO team [78].…”
Section: Observational Constraints On Graviton Mass From Observationsmentioning
confidence: 78%
“…[2016] also use a similar phenomenological consequence of massive gravity and show that an analysis of bright star trajectories near the Galactic Center could bound the graviton mass. They found the upper bound for graviton mass from their work to be m g < 2.9 × 10 −21 eV within 90% confidence level [46,47].…”
Section: Introductionmentioning
confidence: 82%
“…The LIGO -Virgo collaboration together with its partner groups observing the same astronomical sources with different facilities found that constraints on speed of gravitational waves from binary [113]. Since graviton energy is E = hf , therefore, assuming a typical LIGO frequency range f ∈ (10, 100), from the dispersion relation one could obtain a graviton mass estimate m g < 3 × (10 −21 − 10 −20 ) eV which is a weaker estimates than previous ones obtained from binary black hole signals detected by the LIGO team [114]. In the case of massive graviton, one could use Yukawa gravitational potential in a form ∝ r −1 exp(−r/λ g ), and in this case a lower bound for Compton wavelength λ g of the graviton is connected with an upper bound of its mass…”
Section: Massive Graviton Constraintsmentioning
confidence: 99%